Grouper TRAF5 exerts negative regulation on antiviral immune response against iridovirus. Issue 115 (August 2021) - Sun, Mengshi; Wu, Siting; Zhang, Xin; Zhang, Luhao; Kang, Shaozhu; Qin, Qiwei; Wei, Jingguang
Abstract: Tumor necrosis factor receptor-associated factor 5 (TRAF5) is an intracellular protein that binds to the cytoplasmic portion of tumor necrosis factor receptors and mediates the activation of downstream nuclear factor-kappa B (NF-κB), interferon regulatory factor 3, and mitogen activated protein kinase signaling pathways. Compared with other TRAF proteins, TRAF5 is largely unknown in teleosts. In the present study, a TRAF5 homologue (HgTRAF5) from the hybrid grouper ( Epinephelus fuscoguttatus♂ × Epinephelus lanceolatus ♀) was cloned and characterized. The open reading frame of HgTRAF5 consists of 1743 nucleotides encoding a 581 amino acid protein with a predicted molecular mass of 64.90 kDa. Similar to its mammalian counterpart, HgTRAF5 contains an N-terminal RING finger domain, a zinc finger domain, and a C-terminal TRAF domain, including a coiled-coil domain and a MATH domain. HgTRAF5 shares 99.83% identity with giant grouper ( Epinephelus lanceolatus ) TRAF5. Quantitative real-time PCR analysis indicated that HgTRAF5 mRNA was broadly expressed in all examined tissues. The expression of HgTRAF5 increased after Singapore grouper iridovirus (SGIV) infection in grouper spleen (GS) cells. Intracellular localization analysis demonstrated that the full-length HgTRAF5 protein mainly distributed in the cytoplasm. HgTRAF5 overexpression also promoted SGIV replication during viral infection in vitro. HgTRAF5 significantly promoted the activities of interferon-β, interferon-sensitive response element, and NF-κB. Taken together, these results are important for a better understanding of the function of TRAF5 in fish and reveal its involvement in the host response to immune challenge by SGIV. Highlights: HgTRAF5 mRNA was broadly expressed in all examined tissues. HgTRAF5 were identified as a cytosolic protein. HgTRAF5 enhanced SGIV replication during viral infection.